Kualitas dendeng sapi giling pada penambahan gula yang berbeda - Evanuarini, Herly; Huda, Huda (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2011)
ABSTRACT: The aim of this study was to find out the effect of addition sugar to the dendengs’ quality. This research consisted of one level of experiment was designed in Fully Randomized  Design. The result showed that sugar addition gave highly significant effect (P< 0.01) on moisture content and water activity content. The best product was produced by adding 30 % sugar.This product had moisture content value of 13,73 % and water activity value of 0.539. Keywords : Dendeng giling, sugar